Antimicrobial and cytotoxicity activities of sterculia parviflora - Rozmi, Muhammad Syamil; Bakhtiar, M. Taher; Darnis, Deny Susanti (2014)
In this modern world, plants and natural resources are being so significant in various pharmacological and drug research. The search for new antimicrobial and anticancer remedies is among the most prominent research fields nowadays. The aims of the present study are to evaluate the antimicrobial and cytotoxic activity of Sterculiaparviflora against the selected microorganisms and breast cancer cell line (MCF-7) respectively. S. parviflora’s leaves were extracted with n-hexane, ethyl acetate and methanol by using Soxhlet apparatus. At first, the extracts were analyzed for their phytochemical constituents such as alkaloids, flavonoids, saponins, steroids, terpenoids and phenolic. In the antimicrobial screening, the crude extracts were evaluated through disc diffusion and micro dilution methods against two Gram-positive bacteria (S. aureus and B. cereus), two Gram-negative bacteria (P. aeruginosa and E. coli) and two fungi (C. albicanand Aspergillus spp.). In disc diffusion method, the methanol extract exhibited antimicrobial potency against S. aureus and B. cereus which ranged within 8 to 10.7 mm of inhibition zone while ethyl acetate only inhibited B. cereus ranged within 14.7 to 26.3 mm. The Minimum Inhibitory Concentration (MIC) values of methanol extract against both S. aureus and B. cereus is 25 mg/mL while 50 mg/mL against B. cereus for ethyl acetate. The Minimum Bactericidal Concentration (MBC) values which indicated completely inhibition without visible growth of bacteria is at concentration of 50 mg/mL for methanol extract against both S. aureus and B. cereus while 100 mg/mL for ethyl acetate extract against B. cereus. In cytotoxicity study, MTT assay and tryphan blue exclusion methods were done to assess the percentage of viable cells of MCF-7 cell line after being treated with S. parviflora extracts. The results showed that all extracts did not exhibit significant cytotoxic effect on MCF-7 cancer cell line at concentrations of 100, 50, 25, 12.5, 6.25 and 3.125 mg/mL after 24 hours incubation. Moreover, the IC50 values of each extracts also would not be determined due to inability of extracts to reduce the viable cells percentage to be lower than 50%. In conclusion, the S. parviflora extracts exhibited potential antimicrobial activity against S. aureus and B. cereus while possessed no cytotoxic potency against MCF-7 breast cancer cell line.